2007
DOI: 10.1080/17290376.2007.9724815
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of orphan care in Amach, Uganda: assessing policy implications

Abstract: Uganda is estimated to have around two million orphans constituting approximately 19% of all the children in the country. This paper presents findings from a study on the experiences of orphan care among Langi people of Amach sub-county in Lira District, northern Uganda, and discusses their policy implications. The study utilised the following methods in data collection: eight months of ethnographic fieldwork; 21 in-depth interviews with community leaders; 45 with heads of households caring for orphans; 35 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…One explanation might be that the consequence of unfair food equity is more tangible and immediately obvious to neighbors and support organizations such as AFC, while the work requirement may be less apparent and/or more culturally tolerated. In addition, there is some suggestion in the literature that in crisis fostering arrangements, the fostered child's labor is deemed to provide the “reciprocity” missing in voluntary arrangements (Oleke et al., ; Oleke, Blystad, Rekdal, & Moland, ; World Health Organization, ). It is also possible that through income‐generating opportunities, adults are away from home more, leaving the bulk of the household chores to the children.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation might be that the consequence of unfair food equity is more tangible and immediately obvious to neighbors and support organizations such as AFC, while the work requirement may be less apparent and/or more culturally tolerated. In addition, there is some suggestion in the literature that in crisis fostering arrangements, the fostered child's labor is deemed to provide the “reciprocity” missing in voluntary arrangements (Oleke et al., ; Oleke, Blystad, Rekdal, & Moland, ; World Health Organization, ). It is also possible that through income‐generating opportunities, adults are away from home more, leaving the bulk of the household chores to the children.…”
Section: Discussionmentioning
confidence: 99%
“…Probing how children become orphans, studies mostly highlight HIV/AIDS as a prevalent factor (Campbell et al, 2010; Oleke et al, 2007; Tanga, 2013). However, after looking more in depth, serval reasons emerged such as violence in homes, accidents, disasters, abuse, poverty, neglect, family separation, limited services, and deteriorating conditions (Makhonza et al, 2019).…”
Section: Background and Literaturementioning
confidence: 99%
“…Hence, various countries developed a national response for the issue of orphans (Monasch et al, 2007; Oleke et al, 2007). This includes identifying stakeholders, developing action plan, and ensuring government commitment to deal with the cause.…”
Section: Background and Literaturementioning
confidence: 99%
“…It is becoming clear that the challenges of service programming for orphans and vulnerable children call for close attention to the attitudes and needs of elderly members of African rural communities who carry a large proportion of the burden of care (Oburu & Palmerus, ), and to the dynamics of sociocultural change in patterns of distributed responsibility for child care and socialization (Weisner, ). While some surveys have concluded that Africa's renowned extended family system may be collapsing under the excessive pressure of a dramatic increase in the number of orphans (Monasch & Boerma, ), a more productive focus of research is to explore its potential resilience and adaptability to the challenges of the pandemic (Abebe & Aase, ; Kilbride & Kilbride, ; Oburu, ; Oleke, Blystad, Rekdal, & Moland, ).…”
Section: Lessons Learnedmentioning
confidence: 99%